The Impact of House Prices on Household Debt When Controlling for Home Ownership - Dag Henning Jacobsen; Bjørn Helge Vatne (Norges Bank, 2011)
We analyze the effect of house price changes on debt secured on dwellings in Norway. To this end, we use both macro time series and micro panel data. With the intention of being both a cross-check and motivation for the micro analysis, we estimate a structural vector auto regression using macro variables. A key result of the macro analysis is that positive house price innovations have positive and persistent effects on households debt secured on dwellings. Results from the micro data analysis suggest that the effect of house price changes on the borrowing decision differs from the effect on the instalment decision among existing home owners. These results are further investigated trough a two stage model where we control for income, collateral value and age. The model predicts that the size of both loans and instalments increase with income. Loan sizes increase and the instalments fall with increasing collateral value. The results support the existence of a wealth channel but do not provide support for a collateral channel.
hdl:11250/2496954
Keywords: C25; C32; D12; D14; E21; 330; VAR; house prices; mortgage equity withdrawal; logit model; micro panel data